(untitled) (Journal of Health, Population and Nutrition, 2010)
Although many African countries, along the equator, receive a great amount of rainfall and possess a dense hydrographic network, access to drinking-water remains a great challenge. In many households, water is used for various purposes, including domestic and crafts activities. According to the World Health Organization, an estimated four billion cases of diarrheoa occurs worldwide, of which 88% are ascribed to unsafe drinking-water. This study aimed at evaluating health risks in the usage of contaminated drinking-water and its relationship with the prevalence of diarrhoeal diseases in Yaoundé, Cameroon. In this cross-sectional epidemiological design, 3,034 households with children aged less than five years were investigated. Households were selected from among 20 representative neighbourhoods out of 105 that made up the city. The study revealed a diarrheoa prevalence of 14.4% (437 diarrheoa cases out of 3,034 children tested). Among various risk factors examined, water-supply modes and quality of drinking-water were statistically associated with diarrheoa cases. Moreover, levels of diarrheoa attacks varied considerably from one neighbourhood to the other. The spatial analysis helped determine neighbourhoods of higher and lower prevalence of diarrheoa in the city. Key words: Cross-sectional studies; Diarrhoea; Disparity; Drinking-water; Risk factors; Water quality; Water pollution; Water supply; Cameroon DOI: 10.3329/jhpn.v28i5.6150 J HEALTH POPUL NUTR 2010 Oct;28(5):424-435